The temporal response to drought in a Mediterranean evergreen tree: comparing a regional precipitation gradient and a throughfall exclusion experiment (GLOBAL CHANGE BIOLOGY, 2013)
Like many midlatitude ecosystems, Mediterranean forests will suffer longer and more intense droughts with the ongoing climate change. The responses to drought in long-lived trees differ depending on the time scale considered, and short-term responses are currently better understood than longer term acclimation. We assessed the temporal changes in trees facing a chronic reduction in water availability by comparing leaf-scale physiological traits, branch-scale hydraulic traits, and stand-scale biomass partitioning in the evergreen Quercus ilex across a regional precipitation gradient (long-term changes) and in a partial throughfall exclusion experiment (TEE, medium term changes). At the leaf scale, gas exchange, mass per unit area and nitrogen concentration showed homeostatic responses to drought as they did not change among the sites of the precipitation gradient or in the experimental treatments of the TEE. A similar homeostatic response was observed for the xylem vulnerability to cavitation at the branch scale. In contrast, the ratio of leaf area over sapwood area (LA/SA) in young branches exhibited a transient response to drought because it decreased in response to the TEE the first 4years of treatment, but did not change among the sites of the gradient. At the stand scale, leaf area index (LAI) decreased, and the ratios of stem SA to LAI and of fine root area to LAI both increased in trees subjected to throughfall exclusion and from the wettest to the driest site of the gradient. Taken together, these results suggest that acclimation to chronic drought in long-lived Q. ilex is mediated by changes in hydraulic allometry that shift progressively from low (branch) to high (stand) organizational levels, and act to maintain the leaf water potential within the range of xylem hydraulic function and leaf photosynthetic assimilation.

Gas exchange and leaf aging in an evergreen oak: causes and consequences for leaf carbon balance and canopy respiration (Tree Physiology, 2012)
Leaves of Mediterranean evergreens experience large variations in gas exchange rates over their life span due to aging and seasonally changing environmental conditions. Accounting for the changing respiratory physiology of leaves over time will help improve estimations of leaf and whole-plant carbon balances. Here we examined seasonal variations in light-saturated net CO2 assimilation (Amax), dark respiration (Rd) and the proportional change in Rd per 10 °C change in temperature (Q10 of Rd) in previous-year (PY) and current-year (CY) leaves of the broadleaved evergreen tree Quercus ilex L. Amax and Rd were lower in PY than in CY leaves. Differences in nitrogen between cohorts only partly explained such differences, and rates of Amax and Rd expressed per unit of leaf nitrogen were still significantly different between cohorts. The decline in Amax in PY leaves did not result in the depletion of total non-structural carbohydrates, whose concentration was in fact higher in PY than CY leaves. Leaf-level carbon balance modeled from gas exchange data was positive at all ages. Q10 of Rd did not differ significantly between leaf cohorts; however, failure to account for distinct Rd between cohorts misestimated canopy leaf respiration by 13% across dates when scaling up leaf measurements to the canopy. In conclusion, the decline in Amax in old leaves that are close to or exceed their mean life span does not limit the availability of carbohydrates, which are probably needed to sustain new growth, as well as Rd and nutrient resorption during senescence. Accounting for leaf age as a source of variation of Rd improves the estimation of foliar respiratory carbon release at the stand scale.
10.1093/treephys/tps020